Hyponatremia is a marker of disease severity in HIV-infected patients: a retrospective cohort study. Issue 1 (December 2017) - Braconnier, Philippe; Delforge, Marc; Garjau, Maria; Wissing, Karl; De Wit, Stéphane
Abstract Background Hyponatremia is a frequent electrolyte disorder in HIV-infected patients with a prevalence of up to 56% in the pre-cART era. Several studies have demonstrated that patients with hyponatremia are at an increased risk of death. We aimed to investigate the prevalence of hyponatremia in the recent cART-era and evaluate its association with mortality. Methods Single-center retrospective cohort study. A total of 1196 newly diagnosed and cART-naïve HIV patients followed at the AIDS Reference Center, St Pierre University Hospital in Brussels, Belgium, between 1 January 1998 and 31 December 2013 were included. Hyponatremia was defined as a baseline natremia lower than 135 mmol/l. The outcome of interest was the occurrence of death. Results In this study 177 (14.8%) patients had hyponatremia at baseline with a median natremia of 132.0 mmol/l [interquartile range (IQR) 130.0-134.0 mmol/l]. Hyponatremic patients had a lower CD4 cell count (207.5 ± 197.7/μl vs 400.4 ± 277.0/μl;P  < 0.0001) and a higher prevalence of AIDS (50.3% vs 12.4%;P  < 0.0001) compared to normonatremic patients. A significantly higher proportion of patients with hyponatremia were hospitalized at first contact (72.3% vs 20.0%;P  < 0.0001). During the follow-up hyponatremic patients had a shorter median time to a first hospitalization (2.0 IQR [0.0-12.0] months vs 13.0 IQR [2.0-29.0] months;P  = 0.001) and an increased incident hospitalization rate (785/1000 patient-years, 95% CI 725–845 vs 370/1000 patient-years, 95% CI 352–388;P  < 0.0001]. The incident mortality rate was 28.3/1000 patient-years (95% CI 18.15-42.16) in patients with hyponatremia compared to 9.33/1000 patient-years (95% CI 6.63-12.75) in normonatremic patients (P  < 0.0001). Three-year cumulative survival rates were 85.8% ± 3.0% in hyponatremic patients and 96.3% ± 0.7% in normonatremic patients (log-rankP  < 0.0001). However, in a multivariate Cox model adjusting for other risk factors such as AIDS, CD4 count < 350/μl and hepatitis C, hyponatremia was no longer a predictor for patient death (hazard ratio: 1.03, 95% CI 0.54-1.97;P  = 0.935). Conclusions Hyponatremia is a marker of severity of HIV-disease but not an independent risk factor for mortality. HIV-patients with a low serum sodium at baseline might benefit from a close follow-up to improve outcomes.